Public Sociology at its best: A review of Nandini Sundar’s The Burning Forest: India’s War in Bastar (Juggernaut Publication, 2016). - Juhi Tyagi (Journal of Public and Professional Sociology)
This piece reviews a recent book, The Burning Forest, addressing one of the most urgent tasks sociologists have today: of deconstructing the architecture and functioning of democratic states. It also discusses the many dilemmas in public sociology. The author is a prominent Indian public sociologist.